Analisis Peran Perantara terhadap Efisiensi Distribusi Tebu: Studi Kasus Petani Desa Kedungmakam - Melinda Selfi Erdina Putri; Marsono Marsono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The distribution of sugarcane from farmers to sugar mills in Indonesia continues to face various challenges, particularly in terms of logistical efficiency and farmers’ dependency on intermediaries. This study aims to analyze the role of intermediaries in determining the efficiency of sugarcane distribution, using a case study in Kedungmakam Village, Tuban Regency. A qualitative approach with a case study design was employed, enabling an in-depth understanding of distribution practices directly in the field. Data were collected through field observations, in-depth interviews with farmers, intermediaries, and retail traders, as well as supporting documentation. The results indicate that intermediaries play a crucial role in providing production capital, scheduling harvests, and managing transportation of sugarcane to the mills. However, their dominance, in the absence of formal contracts, creates relationship imbalances and weakens the bargaining position of farmers. Furthermore, geographical barriers, limited access to market information, and the lack of independent distribution infrastructure exacerbate inefficiencies and reduce fairness in the existing distribution system. Therefore, strengthening farmer institutions, improving contract transparency, and enhancing access to logistics and information are recommended as long-term solutions.